PRASCAL: a pataphysical programming language. (2016) - Hugill, Andrew; Yang, Hongji
This paper introduces PRASCAL, a programming language that distorts traditional PASCAL using pataphysical principles. The aim of the language is to stimulate creativity and to embed playfulness in computer systems. A wider aim is to reach towards a less severe, more human, form of logic. Pataphysics was a concept elaborated by the French writer and poet Alfred Jarry (1873-1907) in a series of plays and novels, as well as through his own life. It is defined as the science of imaginary solutions and the science of the laws governing exceptions and contradictions. PRASCAL applies this concept through mechanisms such as patadata and Uboolean logic to arrive at a language which is always exceptional and particular.